Mechanical Properties of Oil Palm (Elaeis Guineensis, Jacq.) Empty Fruit Bunch Fibre-Polypropylene Composites - Low, Ai Lean (1999)
This study aimed to evaluate the suitability of oil palm (Elaeis guineensis, Jacq.) empty fruit bunch fibres, currently an agriculture waste available in abundance as filler in polypropylenes (PP). The effects of fibre loading, fibre size, type of PP and fibre type were investigated. Crude EFB fibres were first shredded into shorter lengths(1 - 3 em)and thermomechanically de fibrillated with the laboratory scale pressurised refiner. The fibres obtained were then screened into three different sizes : Fibres retained on mesh size < 0.5 mm , 0.5 - 1 mm and 1 - 2 mm . For comparison, crude EFB fibres of same sizes were prepared using the similar process except refining.